Metabolic and respiratory chemosensitivity and brain monoaminergic responses to cold exposure in chicks subjected to thermal manipulation during incubation: Impact of embryonic thermal manipulation on cold response - Rocha, Aline C.G. [UNESP]; Patrone, Luis Gustavo A. [UNESP]; Cristina-Silva, Caroline [UNESP]; Silva, Kaoma Stephani da Costa; Bícego, Kênia C. [UNESP]; Szawka, Raphael E.; Gargaglioni, Luciane H. [UNESP] (Elsevier, 2022)
We evaluated ventilation (V˙E), body temperature (TB), oxygen consumption (V˙ O2), respiratory equivalent (V˙E/ V˙ O2), and monoamine concentrations of 14-day-old (14d) male and female chicks from eggs incubated at low (LT, 36 °C), control (CT, 37.5 °C) and high (HT, 39 °C) temperature during the early embryonic phase, to normoxia, hypercapnia and hypoxia under exposure to cold environment (20 °C). At normoxia, acute cold exposure did not affect the ventilatory variables, with the exception of HT males, in which cold prevented the reduced V˙E observed under thermoneutral conditions. Exposure to 20 °C caused a decrease in TB in both sexes, and LT and HT females presented a greater hypothermic response. Hypercapnia combined with cold did not alter the ventilatory variables, but LT females and CT males and females showed a blunted CO2-induced hyperventilation due to a higher V˙ O2, compared to the same groups in thermoneutral conditions. Unlike with thermoneutral conditions, the blunted hypercapnic hyperventilation observed in the HT groups was not observed during cold challenge. CO2 exposure promoted a similar decrease in TB in the thermoneutral and acutely cold exposed groups, while LT females under cold condition presented a blunted hypothermic response. During hypoxia, cold challenge attenuated the increase in V˙E in LT females and HT males, due to changes in VT. Hypoxic metabolic depression was greater in LT females and males and HT males during cold exposure, while no change in V˙E/ V˙ O2 was observed. The only alteration in monoaminergic concentration under cold challenge was an increase in brainstem 5-HIAA and 5-HIAA/5-HT ratio in HT females, and an enhanced 5-HT concentration in HT males. In summary, thermal manipulation during embryogenesis induces 14d old chicks to respond differently to cold stress with LT females and HT males being more sensitive.
Keywords: Body temperature; Broiler; Hypercapnia; Hypoxia; Incubation; Ventilation